Inter-relationship of illness perception, personality and quality of life among type 2 diabetes patients: A cross-sectional survey - Pakri Mohamed, Rafidah Aini; Ibrahim, Norhayati; Budin, Siti Balkis; Omar, Ahmad Marzuki; Kamaruddin, Nor Azmi; Ismail, Rozmi (2016)
Improved psychological aspect among type 2 diabetic patients plays an important role towards an improved quality of life. Therefore, the aim of this study is to determine the inter-relationship of illness perceptions, personality and quality of life of type 2 diabetic patients from the Diabetic Clinic of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). A total of 115 of type 2 diabetic patients were involved in this study. Patients were surveyed using a quantitative questionnaires of Short Form 36 (SF-36), Revised-Illness Perception (IPQ-R) and big five inventory from September to December 2014. Result shows that most of the sub-domains in the Health Related Quality of Life (HRQOL) were correlated either positively or negatively with the sub-domain of illness perceptions (p<0.05). In addition, most of the sub-domains of the Big Five inventory were also positively correlated with the sub-domains of HRQOL except for the neuroticism sub-domain (p<0.05). It was also found that personality contributed 21.2% of the variation to the PCS domain while 32.6% of the variation contributed to the MCS domain ofHRQOL. In addition, 17.1% of the illness perceptions variation contributed to the PCS domain and 32.7% of the variation contributed to the MCS domain of HRQOL. The findings of this study shows that there is a positive inter-relationship between illness perceptions and personality towards the quality of life of type 2 diabetic patients. A better understanding of illness perceptions and positive personality plays an important role in improving the quality of life among type 2 diabetic patients.